Increasing the Efficiency of Education Using Distance Technologies - Nigina, Turakulova; Tuychiyevna, Razikova Lola (International Journal on Orange Technologies, 2023)
This article discusses the use of distance learning technologies, which open up new prospects for the effectiveness of the educational process. The transition of classes to distance learning has become a major problem during the pandemic in 2020. It is important to note that such an unexpected transition to distance learning gave impetus to the development of the pedagogical community. The use of an electronic training course is possible at any time, in a mode and volume that suits a particular student.